Integrating model-in-the-loop simulations to model-driven development in industrial control. (December 2014) - Vepsäläinen, Timo; Kuikka, Seppo
Software applications are becoming increasingly important in automation and control systems. This has forced control system vendors and integrators to pursue new, more effective software development practices. One of the promising research paths has been the utilization of Unified Modeling Language and model-driven development. However, integration of simulations to the existing model-driven development approaches still has not been sufficiently described in the literature. This is surprising as advanced mathematical simulation tools are already in use in the domain to facilitate control algorithm development. In this paper, this issue is addressed by extending a tool-supported model-driven development process with object-oriented, component-based simulation capabilities. To demonstrate the proposed technique, a control system model for a crane system is developed and the technique then used to create a Modelica simulation of the controlled crane.